A Linguistics Analysis of Syntax and Style in Ed Sheeran’s “Perfect” - Amelia Faddya Wildhani; Annajmi Mastari Maryam; Raihani Raihani; Siti Ismahani (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study explores the syntactic and stylistic aspects of Ed Sheeran’s song Perfect (2017) to reveal how grammatical structures contribute to emotional and artistic meaning. Using a descriptive qualitative method, the research analyzes the song’s lyrics based on phrase structure theory and grammatical framework. The analysis focuses on sentence types, phrase patterns, and clause relations. The findings show that declarative sentences dominate the lyrics, expressing sincerity and emotional clarity, while imperative and interrogative forms add variation and intimacy. Noun, verb, and prepositional phrases collectively create vivid imagery and smooth narrative flow. The combination of independent and dependent clauses reflects both certainty and vulnerability, central to the song’s romantic theme. Stylistic devices such as ellipsis and repetition enhance rhythm and emotional depth. Overall, the study concludes that syntax in song lyrics functions beyond structure, shaping style and meaning. The findings also demonstrate the potential of song lyrics as authentic materials for English language teaching.